Microbiome specificity and fluxes between two distant plant taxa in Iberian forests - Saati-Santamaría, Zaki; Vicentefranqueira, Rocío; Kolařik, Miroslav; Rivas, Raúl; García-Fraile, Paula (Environmental microbiome, 2023)
BACKGROUND: Plant-associated microbial communities play important roles in host nutrition, development and defence. In particular, the microbes living within internal plant tissues can affect plant metabolism in a more intimate way. Understanding the factors that shape plant microbial composition and discovering enriched microbes within endophytic compartments would thus be valuable to gain knowledge on potential plant-microbial coevolutions. However, these interactions are usually studied through reductionist approaches (in vitro models or crop controlled systems). Here, we investigate these ecological factors in wild forest niches using proximally located plants from two distant taxa (blueberry and blackberry) as a model. RESULTS: Although the microbial communities were quite similar in both plants, we found that sampling site had a high influence on them; specifically, its impact on the rhizosphere communities was higher than that on the roots. Plant species and sample type (root vs. rhizosphere) affected the bacterial communities more than the fungal communities. For instance, Xanthobacteraceae and Helotiales taxa were more enriched in roots, while the abundance of Gemmatimonadetes was higher in rhizospheres. Acidobacteria abundance within the endosphere of blueberry was similar to that in soil. Several taxa were significantly associated with either blackberry or blueberry samples regardless of the sampling site. For instance, we found a significant endospheric enrichment of Nevskia in blueberry and of Sphingobium, Novosphingobium and Steroidobacter in blackberry. CONCLUSIONS: There are selective enrichment and exclusion processes in the roots of plants that shapes a differential composition between plant species and sample types (root endosphere-rhizosphere). The special enrichment of some microbial taxa in each plant species might suggest the presence of ancient selection and/or speciation processes and might imply specific symbiosis. The selection of fungi by the host is more pronounced when considering the fungal trait rather than the taxonomy. This work helps to understand plant-microbial interactions in natural ecosystems and the microbiome features of plants.
Keywords: Plant microbiome; Soil communities; Blackberry; Host-microbe interactions; Blueberry; Rhizosphere